2005
DOI: 10.1177/0044118x04272290
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Youth Closeness and Youth's Suicidal Ideation

Abstract: Data from a nationally representative sample of adolescents studied at two points in time are used to examine gender-specific influence of parent-youth closeness on youth's suicidal ideation and its variations by stages of adolescence and race or ethnicity. Logistic regression analyses yielded interesting findings: (a) Closeness with fathers exerts an important influence on girls, and this effect is observed regardless of stages of adolescence and race/ethnicity; (b) the influence of fathers on boys declines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…By contrast, father-child closeness is conducive to child positive outcomes. Among AAs, father-child closeness was linked to children's lower risk of suicide ideation (Liu, 2005) as well as increased autonomy, an association stronger than that of mother-child closeness (Kiang & Bhattacharjee, 2019).…”
Section: Impacts Of Aa Father-child Relationships On Child Outcomesmentioning
confidence: 88%
“…By contrast, father-child closeness is conducive to child positive outcomes. Among AAs, father-child closeness was linked to children's lower risk of suicide ideation (Liu, 2005) as well as increased autonomy, an association stronger than that of mother-child closeness (Kiang & Bhattacharjee, 2019).…”
Section: Impacts Of Aa Father-child Relationships On Child Outcomesmentioning
confidence: 88%
“…Closeness with the father in late adolescence is "significantly related to suicidal ideation". [45] Liu goes on to explain the relationship found between closeness with the opposite sex parent and the child's risk of suicidal thoughts. It was found that boys are better protected from suicidal ideation if they are close to their mothers through early and late adolescence; whereas girls are better protected by having a close relationship with their father during middle adolescence.…”
Section: Family Violence Childhood Residential Instabilitymentioning
confidence: 99%